Comparison of maxillomandibular asymmetries in adult patients presenting different sagittal jaw relationships - Guilherme Thiesen; Maria Perpétua Mota Freitas; Bruno Frazão Gribel; Ki Beom Kim
ABSTRACT Objective: The present study aims at using cone beam computed tomography (CBCT) to analyze the maxillomandibular characteristics present in adults with mandibular asymmetries and different sagittal jaw relationships. Methods: 360 patients were selected and divided into three groups (Class I, Class II, and Class III), with 120 individuals per group. The groups were then subdivided according to the intensity of lateral deviation of the gnathion point, into: 1) relative symmetry, 2) moderate asymmetry, and 3) severe asymmetry. Three planes of reference were established in the CBCT images and several measurements were taken to compare the bilateral skeletal differences between the intensities of asymmetry for the different sagittal jaw relationships. Results: When the groups were compared by the intensity of asymmetry, significant differences among patients with relative symmetry and moderate to severe asymmetry were found. This was especially noticed for severe asymmetry, suggesting that the deviation of the chin did not constitute the only morphological alteration for these patients, especially because a series of measurements showed significant bilateral differences. When comparing sagittal jaw relationships, the only significant finding was the vertical positioning of the gonion between Class II and III patients with severe asymmetry. Conclusions: When comparing the three sagittal jaw relationships with the same intensity of asymmetry, most maxillofacial aspects were quite similar. The only difference was found for patients with severe asymmetry, as the individuals with Class II showed greater bilateral difference in the vertical positioning of the gonion, when compared to patients with Class III.